An overview of size reduction technologies in the field of pharmaceutical manufacturing - Patel, Rakesh P; Baria, Ashok H; Patel, Nikunjana A (Asian Journal of Pharmaceutics (AJP), 2014)
Size reduction is a process of reducing large solid unit masses into small unit masses, coarse particles or fine particles. Size reduction process is also termed as comminution or diminution or pulverizations. In addition to the standard adjustments of the milling process (i.e., speed, screen size, design of rotor, load), special techniques of milling may be useful including special atmosphere, temperature control, sonocrystallization, supercritical fluid process. etc. Moreover, some advance technologies of size reduction including Micron Technologies, Gran-U-LizerTM Technology, Jet-O-MizerTM and MicrofluidicsÂ® have been popular. Various application of size reduction concept covers oral delivery of poorly soluble drugs, micronization, nanotechnology (micro- and nano suspensions), etc.This systemic review highlights advantages and disadvantages, mechanisms, theories, techniques, advances, and pharmaceutical applications of size reduction technology.